Adult Education as Building Community: The Parameters and Realities of Enterprise Identity in North America (1945-70) - André P. Grace (Adult Education Research Conference, 1998)
This paper takes up aspects of building community in North American adult education (1945-70). It looks at adult education’s efforts to build community in itself and explores the degree to which the enterprise built community in education and society.